2021
DOI: 10.1111/aec.12995
|View full text |Cite
|
Sign up to set email alerts
|

A functional trait‐based approach to assess the impact of an alien palm invasion on plant and soil communities on a South Pacific island

Abstract: In island ecosystems, biological invasions are one of the major threats to native biodiversity and to ecosystem functioning. Invasive ornamental plants such as the alien palm tree Pinanga coronata in the Fiji islands can form mono-dominant stands in rainforests and displace native species. Using a functional trait-based approach, we investigated the impact of P. coronata on both above and belowground communities (i.e. plants and Collembola). Within a rainforest reserve on Fiji´s principal island, we sampled a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Responses within the soil fauna also differ between trophic levels and life-forms, potentially leading to different food-web structures and performances. Our results reveal the need to further investigate belowground response to IAP because, in the context of biological invasions, the importance of plant species' identity and composition as drivers of soil biodiversity is predominant [6,61]. This is most likely explained by trait differences between plant species, which can determine litter quality and physical structure, with subsequent consequences for trophic resources and microhabitat conditions [6,62].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Responses within the soil fauna also differ between trophic levels and life-forms, potentially leading to different food-web structures and performances. Our results reveal the need to further investigate belowground response to IAP because, in the context of biological invasions, the importance of plant species' identity and composition as drivers of soil biodiversity is predominant [6,61]. This is most likely explained by trait differences between plant species, which can determine litter quality and physical structure, with subsequent consequences for trophic resources and microhabitat conditions [6,62].…”
Section: Discussionmentioning
confidence: 93%
“…Briefly, while plants provide organic matter to the belowground system, soil organisms, e.g., soil fauna and soil microorganisms, through decomposition and mineralization processes, regulate the delivery rate of nutrients back to the plants. Recently, Forey et al [6] showed that an invasive palm tree, Pinanga coronata, on a South Pacific Island, led to weakening of the plant-soil fauna relationships (i.e., trait-matching) compared to the more stable relationships in noninvaded plots. In different recent meta-analyses, it was shown that habitat-context, mainly open (e.g., meadows) versus closed habitats (e.g., forests), strongly interact with the trophic position of an organism to determine the response of soil fauna to the presence of invasive species, and that stronger responses were observed in open habitats [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The key topics relative to the location in each country are represented in Figure 2. Also of interest are the publications coming from under‐represented Southern Hemisphere countries including Madagascar (Hending et al, 2021; Santos & Ribeiro, 2022), Fiji (Forey et al, 2021; Harlow et al, 2022; Wright et al, 2021), Peru (Doan et al, 2021) and Uruguay (Boltovskoy et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it is possible that P. coronata acts as an ecosystem engineer by changing ecosystem functioning and affecting other trophic levels which, in turn, filters plants in the ecosystem. For example, Forey et al (2021), in the same forest, demonstrated that P. coronata led to a change in soil fauna communities (i.e., Collembola) and suggested a decrease in plant-soil interactions under P. coronata invasion.…”
Section: Pinanga Coronata 'S Effect On Plant Traits and Strategies Of...mentioning
confidence: 99%
“…Among these, the non-native ivory cane palm Pinanga coronata (Blume ex Mart.) Blume (Arecaceae family) has considerable potential to fundamentally change the structure and diversity of the archipelago's rainforests (Dyer et al 2018(Dyer et al , 2019Forey et al 2021;Keppel and Watling 2011). In forest habitats, P. coronata has a strong advantage over understory species in competing for light due to its taller stature and architectural adaptation to shaded conditions (Kimura and Simbolon 2002).…”
Section: Introductionmentioning
confidence: 99%